Contextualization of Employment of Zakat Form The Perspective of Mafhum Muwafaqah - Suwarjin (Nusantara: Journal of Law Studies, 2023)
This study describes the contextualization of the utilization of zakat assets based on the current context so that zakat assets can be used as social instruments in overcoming various problems faced by modern Muslim society. The method used is the Mafhum Muwafaqah, which extends the meaning of a text from the explicit meaning to the implied meaning as long as the meaning is still correlated with the explicit meaning. No research results have explained this object using the understanding of the muwafaqah approach, so this research contains an element of novelty. This Article concluded that the eight ashnaf targets of zakat as mentioned in the verse in sura al-Maidah 63, are not limited in nature but can be expanded in the scope of meaning. Poor-poor Ashnaf can expand its scope to fund home renovations, pay mortgages/home loans, and pay BPJS Health and BPJS Employment contributions. Muallaf are not limited to people but can expand their reach to legal entities or social institutions, such as muallaf centres, efforts to stem Christianization, publishing books to enlighten people prone to apostasy and others. Freeing enslaved people can broaden the scope of its meaning by providing employment for migrant workers and providing legal assistance to migrant workers who are involved in legal problems in other countries. Gharimin can expand its scope to charitable and philanthropic institutions, Sabilillah can expand to strategic community projects, such as water pipe connections clean, and Ibnu Sabil can expand its reach to provide comfort to volunteers handling natural disasters